2015
DOI: 10.1002/hec.3264
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Regional‐level Factors Contributing to Variation in Length of Stay After Cerebral Infarction in Six European Countries

Abstract: Using patient-level data for cerebral infarction cases in 2007, gathered from Finland, Hungary, Italy, the Netherlands, Scotland and Sweden, we studied the variation in risk-adjusted length of stay (LoS) of acute hospital care and 1-year mortality, both within and between countries. In addition, we analysed the variance of LoS and associations of selected regional-level factors with LoS and 1-year mortality after cerebral infarction. The data show that LoS distributions are surprisingly different across countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
5
11
0
2
Order By: Relevance
“…Azokat a módszertani kérdéseket emeltük ki, amelyek a jelen lapszámban megjelenő AMI, STR, HIP és VLBW diagnóziscsoportokkal kapcsolatos közle ményeink értelmezéséhez szükségesek. A EuroHOPE kutatás egyéb területeit a nemzetközi publikációkból [3][4][5][6][7][8][9][10][11][12] és a kutatás honlapjáról lehet megismerni (http://www.eurohope.info). Az egyes diagnóziscso portok specifikus módszertani jellemzőit a témát ismer tető dolgozatokban közöljük.…”
Section: öSszefoglaló Közleményunclassified
See 1 more Smart Citation
“…Azokat a módszertani kérdéseket emeltük ki, amelyek a jelen lapszámban megjelenő AMI, STR, HIP és VLBW diagnóziscsoportokkal kapcsolatos közle ményeink értelmezéséhez szükségesek. A EuroHOPE kutatás egyéb területeit a nemzetközi publikációkból [3][4][5][6][7][8][9][10][11][12] és a kutatás honlapjáról lehet megismerni (http://www.eurohope.info). Az egyes diagnóziscso portok specifikus módszertani jellemzőit a témát ismer tető dolgozatokban közöljük.…”
Section: öSszefoglaló Közleményunclassified
“…A nemzetközi összehasonlító elemzéseket számos publi kációban [3][4][5][6][7][8][9][10][11][12] közöltük, a részletes publikációs jegy zék ugyancsak elérhető a EuroHOPE honlapján.…”
Section: áBraunclassified
“…It was shown that the choice of reference data had little impact on outcomes (Moger and Peltola, 2014). In studies reported in two papers, the regional-level analysis was supplemented with analyses using the pooled patient-level data from five countries (Hagen et al, 2015b;Peltola et al, 2015), whereas in the studies reported in two other papers, solely pooled patient-level data were used Kittelsen et al, 2015).…”
Section: Risk Adjustmentmentioning
confidence: 99%
“…Five specific diseases (acute myocardial infarction (AMI), breast cancer, hip fracture, stroke and infants born with very low birth weight (VLBW) and/or very low gestational age (VLGA) (further referred to as VLBW/VLGA infants) were selected to serve as case studies and for which countrywide patient data were collected in the participating countries (Finland, Hungary, Italy, 1 the Netherlands, Norway, Scotland and Sweden) Hagen et al, 2015aHagen et al, , 2015bMalmivaara et al, 2015;Medin et al, 2015;Numerato et al, 2015;Peltola et al, 2015;Smith et al, 2015). Five specific diseases (acute myocardial infarction (AMI), breast cancer, hip fracture, stroke and infants born with very low birth weight (VLBW) and/or very low gestational age (VLGA) (further referred to as VLBW/VLGA infants) were selected to serve as case studies and for which countrywide patient data were collected in the participating countries (Finland, Hungary, Italy, 1 the Netherlands, Norway, Scotland and Sweden) Hagen et al, 2015aHagen et al, , 2015bMalmivaara et al, 2015;Medin et al, 2015;Numerato et al, 2015;Peltola et al, 2015;Smith et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation